10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
IntroductionRates of sudden cardiac death (SCD) on ski slopes have been increasing since the 1980's and is the most common cause of nontraumatic death in male skiers. The treatment for SCD is early cardiopulmonary resuscitation (CPR) and difbrillation. Quality CPR, defined as adequate rate, depth, location, and with minimal interruptions, has been shown to improve outcomes. SCD on ski slopes often requires transport down the ski hill on a toboggan, for which manual compression trials have demonstrated inferior CPR quality.MethodsThis was conducted as a prospective, crossover study from November 2024-May 2025. CPR metrics were recorded with a Bluetooth-capable CPR mannikin. Each trial consisted of 2 runs down a specified route with manual compression-only CPR versus mechanical compressions.Results10 trials were conducted, and 9 trials were completed. 3 patrollers were ejected from toboggans while performing manual compressions in three separate trials. Mechanical CPR demonstrated significantly superior compression fraction, compression rate, and correct compression position. There was no significant difference in total scenario time, compression depth, or pause time.ConclusionsThis study demonstrates potential benefits of mechanical CPR in ski patrol toboggans, including rescuer safety, and improved CPR metrics while moving in sustained, complex terrain.